Patient Satisfaction in Elective Major Surgery for Benign Disease in a Tertiary Care Hospital. - Maharjan, Shanta Bir; Lamichhane, Deep; Joshi, Arbin; Shah, Sashi; Thapa, Ghanshyam; Shah, Jay N (Medical Journal of Shree Birendra Hospital, 2013)
Introduction: Since civilization physicians are upheld at high standard to promote interests of patients and society. In this study we aimed to analyze issues related to patient satisfacti on for better patient care. Methods: There were 145 surgical patients in this cross sectional prospective observational study for elective benign disease. Patient’s response to pre-tested questionnaire before and after surgery was scored was on a 3-point scale. Variables included patient demographics; diagnosis, treatments, complications; counseling, social, financial concern; surgeon’s competency, hospital facilities, pain management and overall satisfaction. Microsoft Excel was used for descriptive analysis. Results: Average age of patients was 44 years and male were 42.7% (62/145). All patients were satisfied for information on diagnosis, complications and hospital facilities. Patients consented for surgery themselves in 96.5%. Financial concern was found in 17.3% and inadequate pain management in 7.6%. Overall,96.5% patients were satisfied. Conclusions: Even though 96.5% patients were satisfied, further analysis revealed there is room for improvement on post-operative pain management (in 17.3%) and financial constrains (in 7.6%) in elective major surgery for benign diseases in our setup. Medical Journal of Shree Birendra Hospital; Jan-June 2012/vol.11/Issue1/9-12 DOI: http://dx.doi.org/10.3126/mjsbh.v11i1.7759